The Existence of Gus Iqdam’s Dakwah in the Spiritual Preferences of the Young Generation - Agustina, Indah Yulia; Hidayat, Nadia Amalia; Novianti, Fatma (Proceedings of International Conference on Muslim Society and Thought, 2024)
In rapid changes in the digital world, da’wah as an effort to spread religious values is also required to keep up with the development of information technology. Currently, many preachers utilize social media, especially Tik Tok, to attract the participation of the younger generation who are already very familiar with social media. Various styles of da’wah are offered as a characteristic of each preacher. The author focuses the research study on one of the preachers quite famous among the younger generation, Gus Iqdam. This study aims to review more deeply the existence of Gus Iqdam’s preaching in the spiritual preferences of the younger generation. The research method used is a qualitative approach. Data collection was carried out through observation of the Tik Tok social media content of Majelis Sabilu Taubah @hadrohsabilutaubah, then the data was analyzed using content analysis. The results showed the central role of a figure, namely Gus Iqdam, who has a distinctive and contemporary characteristic in delivering da’wah. He can attract the participation of the wider community, especially the younger generation. Gus Iqdam’s da’wah style is adapted to the spiritual preferences of today’s younger generation. On the fifth day of Harlah, Majelis Taklim Sabilu Taubah invited singers who were trending among young people to enliven the event. In the perspective of the spiritual marketplace theory developed by Wade Clark Roof, this shows the synergy between worldly interests and the spirituality of the generation of seekers.